Penerapan Modul Ajar Bahasa Indonesia pada Siswa Kelas X SMK Negeri Simpang Empat di Tanah Bumbu (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2026)
This study aims to analyze the effectiveness, challenges, and solutions of the application of the Indonesian teaching module of biographical text material in grade X students of SMK Negeri Simpang Empat Tanah Bumbu in the Independent Curriculum. Teaching modules, which are essential for systematic planning, are often difficult for teachers to compile. This module focuses on the development of listening and speaking skills, as well as the cultivation of the Pancasila Student Profile (independent, critical, creative), supported by students' initial knowledge, various media, and a Creative-Productive learning model. With qualitative methods, the study found that although the teaching modules succeeded in creating planned learning (through activities such as goal negotiations, video exploration, and group discussions), there were major challenges in integrating all elements effectively, optimizing students' initial knowledge, developing independence/critical thinking, and overcoming media constraints and classroom dynamics. Therefore, this study emphasizes the need for teacher innovation in compiling and implementing modules so that learning becomes even, interesting, and in accordance with the spirit of the Independent Curriculum.